Billroth und Brahms: Medizin und Musik in der persönlichen Begegnung - Hadaschik, Boris; Hadaschik, Eva; Hohenfellner, Markus (Der Urologe, 2012)
Theodor Billroth and Johannes Brahms shared a decades long personal friendship. The music-loving Billroth influenced the work of the famous composer and in turn Brahms also left traces within Billroth’s lifetime achievements. To shed light on the close relationship of medicine and music, this manuscript describes both Billroth’s life and surgical career as they were influenced and stimulated by his close friendship to Brahms.Theodor Billroth and Johannes Brahms first met in 1865 in Zurich, Switzerland. After Billroth accepted the chair of surgery at the University of Vienna in 1867, Brahms moved to Vienna in 1869. During the following years, Billroth analyzed most of Brahms’ compositions prior to publication. Similar to his effective way of teaching medical students and assistants, Billroth stimulated Brahms to publish many of his later compositions. Brahms on the other hand supported Billroth in writing his essay“Who is musical?”. Furthermore, music helped Billroth to cope with the demanding working life of a surgeon.Music and surgery share both structural and emotional analogies. While both professions require meticulous techniques, personal interaction is a prerequisite for success. “Science and art scoop from the same well.”